Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(-27.43+x=27.57\)\(\Leftrightarrow x=27.57-\left(-27.43\right)\)
\(\Leftrightarrow x=27.57+27.43\)\(\Leftrightarrow x=27.\left(57+43\right)\)
\(\Leftrightarrow x=27.100\)\(\Leftrightarrow x=2700\)
Vậy \(x=2700\)
b) \(3\left(x-2\right)+5\left(3-x\right)=3\)\(\Leftrightarrow3x-6+15-5x=3\)
\(\Leftrightarrow3x-5x=3+6-15\)\(\Leftrightarrow-2x=-6\)\(\Leftrightarrow x=3\)
Vậy \(x=3\)
c) \(3^x=27\)\(\Leftrightarrow3^x=3^3\)\(\Leftrightarrow x=3\)
Vậy \(x=3\)
d) \(2^x+17=-15\)\(\Leftrightarrow2^x=-32\)( vô nghiệm )
Vậy \(x\in\varnothing\)
e) \(\left(x-2\right)^2=9\)\(\Leftrightarrow\orbr{\begin{cases}x-2=-3\\x-2=3\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=-1\\x=5\end{cases}}\)
Vậy \(x=-1\)hoặc \(x=5\)
f) \(\left(x-2\right)^3=27\)\(\Leftrightarrow\left(x-2\right)^3=3^3\)\(\Leftrightarrow x-2=3\)\(\Leftrightarrow x=5\)
Vậy \(x=5\)
g) \(\left(x-2\right)^3=-27\)\(\Leftrightarrow\left(x-2\right)^3=\left(-3\right)^3\)\(\Leftrightarrow x-2=-3\)\(\Leftrightarrow x=-1\)
Vậy \(x=-1\)
a) \(\left(19x+2\times5^2\right):14=\left(13-8\right)^2-4^2\)
\(\Rightarrow\left(19x+50\right):14=5^2-4^2=25-16=9\)
\(\Rightarrow19x+50=126\)
\(\Rightarrow19x=76\Rightarrow x=4\)
Vậy x = 4
b) \(2\times3^2=10\times3^{12}+8\times27^4\)
\(\Rightarrow2\times3^2=10\times\left(3^3\right)^4+8\times27^4\)
\(\Rightarrow2\times3^2=27^4\times\left(10+8\right)\)
\(\Rightarrow18=27^4\times18\)
\(\Rightarrow27^4\times18-18=0\Rightarrow18\times\left(27^4-1\right)=0\)
=> Không thấy biến x đâu cả
c) Ta thấy 33 = 27
\(\Rightarrow3^{2x-5}=3^3\Rightarrow2x-5=3\Rightarrow2x=8\Rightarrow x=4\)
Vậy x = 4
d) \(3^{x+1}-x=80\Rightarrow3^{x+1}=81\)
Ta thấy 34 = 81
\(\Rightarrow3^{x+1}=3^4\Rightarrow x+1=4\Rightarrow x=3\)
Vậy x = 3
a) \(3^x=81\)
\(3^x=3^4\)
\(\Rightarrow x=4\)
b) \(2^x.16=128\)
\(2^x=128:16\)
\(2^x=8\)
\(2^x=2^3\)
\(\Rightarrow x=3\)
c) \(3^x:9=27\)
\(3^x=27.9\)
\(3^x=243\)
\(3^x=3^5\)
\(\Rightarrow x=5\)
d) \(x^4=x\)
\(\Rightarrow x=0\)hoac \(\orbr{\begin{cases}x=1\\x=-1\end{cases}}\)
e) \(\left(2x+1\right)^3=27\)
\(\left(2x+1\right)^3=3^3\)
\(\Rightarrow2x+1=3\)
\(\Rightarrow2x=4\)
\(\Rightarrow x=2\)
f) \(\left(x-2\right)^2=\left(x-2\right)^4\)
\(\left(x-2\right)^2-\left(x-2\right)^4=0\)
\(\left(x-2\right)^2-\left(x-2\right)^2.\left(x-2\right)^2=0\)
\(\left(x-2\right)^2\left[1-\left(x-2\right)^2\right]=0\)
\(\left(x-2\right)^2\left(1-x+2\right)\left(1+x-2\right)=0\)
\(\Rightarrow\left(x-2\right)^2=0\)hoac \(\orbr{\begin{cases}3-x=0\\x-1=0\end{cases}}\)
\(\Rightarrow x-2=0\)hoac \(\orbr{\begin{cases}x=3\\x=1\end{cases}}\)
\(\Rightarrow x=2\)hoac \(\orbr{\begin{cases}x=3\\x=1\end{cases}}\)
a) \(3^x=81\Leftrightarrow3^x=3^4\Rightarrow x=4\)
b)\(2^x\times16=128\Leftrightarrow2^x=8\Leftrightarrow2^x=2^3\Rightarrow x=3\)
c) \(3^x\div9=27\Leftrightarrow3^x\div3^2=3^3\Rightarrow x=5\)
d) \(x^4=x\Leftrightarrow x=1\)
e) \(\left(2x+1\right)^3=27\Leftrightarrow\left(2x+1\right)^3=3^3\Rightarrow2x+1=3 \)
\(\Rightarrow2x=3+1\Leftrightarrow2x=4\Rightarrow x=2\)
F)
1 ) 2.3x - 5 = 72 <=> 2.3x - 5 = 49 <=> 2.3x = 54 => 3x = 27 = 33 => x = 3
2 ) 3x + 1 = 27 => 3x + 1 = 33 => x + 1 = 3 => x = 2
3 ) 5x-2 = 1 = 50 => x - 2= 0 => x = 2
4 ) 9x-1 = 1 = 90 => x - 1 = 0 => x = 1
1)2.3^x-5=49=>2.3^x=54=>3^x=27=>x=3
2)3^x+1=26=>x+1=3=>x=2
3)5^x-2=1=>5^0=>x-2=0=>x=2
4)9^x-1=1=>9^0=x-1=0=>x=1
2300 = (23)100 = 8100
3200 = (32)100 = 9100
8100 < 9100
nên 2300 < 3200
a) \(2^{4x+1}-8^{x+2}=0\)\(\Leftrightarrow2^{4x+1}-2^{3\left(x+2\right)}=0\)
\(\Leftrightarrow2^{4x+1}-2^{3x+6}=0\)\(\Leftrightarrow2^{4x+1}=2^{3x+6}\)
\(\Leftrightarrow4x+1=3x+6\)\(\Leftrightarrow4x-3x=6-1\)\(\Leftrightarrow x=5\)
Vậy \(x=5\)
b) \(3^2.9^{2x}=27^{x+3}\)\(\Leftrightarrow3^2.3^{2.2x}=3^{3\left(x+3\right)}\)\(\Leftrightarrow3^2.3^{4x}=3^{3x+9}\)
\(\Leftrightarrow3^{2+4x}=3^{3x+9}\)\(\Leftrightarrow2+4x=3x+9\)\(\Leftrightarrow4x-3x=9-2\)\(\Leftrightarrow x=7\)
Vậy \(x=7\)
c) \(8^{2x}.64^2=16^{x+4}\)\(\Leftrightarrow2^{3.2x}.2^{6.2}=2^{4\left(x+4\right)}\)\(\Leftrightarrow2^{6x}.2^{12}=2^{4\left(x+4\right)}\)
\(\Leftrightarrow2^{6x+12}=2^{4x+16}\)\(\Leftrightarrow6x+12=4x+16\)\(\Leftrightarrow6x-4x=16-12\)
\(\Leftrightarrow2x=4\)\(\Leftrightarrow x=2\)
Vậy \(x=2\)